Lecturer's Performance: The Effect of Leadership Communication, Organizational Culture and Achievement Motivation by Mediating Variables - Suyitno (Yayasan Ilomata, 2024)
Many aspects, such as leadership communication, organizational culture, and, of course, performance, can improve motivation. The goal of this study was to examine the impact of leadership communication and organizational culture on lecturer performance through achievement motivation in tertiary institutions in East Java that administer Islamic boarding schools. This is an explanatory study that use quantitative methodologies. The research data were collected by distributing questionnaires to 146 lecturers and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the SmartPLS 3.0 application. The path analysis results reveal that leadership communication and organizational culture have a direct and substantial effect on lecturer achievement motivation, and that organizational culture and achievement motivation have a direct and significant effect on lecturer performance. In the meanwhile, leadership communication has no direct effect on lecturer performance. The indirect test results also suggest that leadership communication has little effect on lecturer performance through motivation. Similarly, organizational culture has no influence on lecturer performance through achievement motivation. According to the research findings, tertiary institutions' attempts to improve lecturer performance must pay attention to organizational culture and increase lecturer success motivation in order to fully support them in carrying out their operations.